Sistem Pemilihan Umum di Indonesia: Perbandingan antara Sistem Pemilihan Umum Proporsional Terbuka dan Sistem Pemilihan Umum Proporsional Tertutup (SETARA : Jurnal Ilmu Hukum, 2024)
This article examines the general election system in Indonesia by comparing the open proportional system and the closed proportional system. The issue is important because electoral system design strongly influences the quality of representation, party institutionalisation, voter participation, and the broader health of democracy. Using normative juridical research, the article reviews constitutional provisions, election statutes, and scholarly discussion on electoral models used in Indonesia since independence. The study finds that proportional representation has long been considered suitable for Indonesia's plural society, but the shift from a closed to an open proportional system has significantly changed the relationship between parties, candidates, and voters. The open proportional system strengthens direct voter choice and candidate-voter proximity, yet it also intensifies internal competition, campaign costs, and the risk of vote buying. The article concludes that an electorally healthy democracy requires not only an appropriate proportional design, but also stronger political education and firm law enforcement against money politics.
Keywords: General Election System; Open Proportional; Closed Proportional; Electoral Law; Democracy